TRANSFORMATION OF EARLY CHILDHOOD EDUCATION IN THE DIGITAL AGE: THE ROLE OF TEACHERS IN BUILDING EARLY LITERACY IN YOUNG CHILDREN - Helnita, Helnita; Meutia, Raudha; Miharti, Ridha (Department of Early Childhood Education, Universitas Bina Bangsa Getsempena, 2025)
The transformation of learning in Early Childhood Education (PAUD) in the digital age requires a paradigm shift in the teaching and learning process. Teachers are no longer the sole source of information, but rather act as facilitators who utilize technology to create interactive and meaningful learning experiences for children. This study aims to describe the transformation of early childhood education in the digital age and examine the role of teachers in optimizing early literacy development in young children. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation studies at three early childhood education institutions in Banda Aceh. The results of the study show that digital learning transformation in early childhood education is realized through the use of interactive media such as educational videos, children's literacy applications, and digital communication with parents. Teachers play an important role in designing digital-based literacy activities that still pay attention to the principles of developmentally appropriate practice (DAP). In addition, it was found that teachers' digital literacy competencies are a major factor in the success of improving children's early literacy skills, particularly in letter and word recognition and language skills. However, challenges such as limited resources, teacher training, and education policy remain obstacles to implementation. The conclusion of this study emphasizes that the transformation of early childhood education in the digital era requires policy support, strengthening of teacher competencies, and collaboration between educational institutions and parents. Optimizing the role of teachers is key to building a foundation for children's early literacy that includes not only reading and writing skills, but also digital literacy and critical thinking from an early age.